Evaluación de la fragmentación del suelo agrícola y su incidencia en el desarrollo socio económico del barrio Illuchi, parroquia Belisario Quevedo, cantón Latacunga, provincia de Cotopaxi año 2014 - Tovar Cobo, César Eduardo (2015)
This research helps to understanding the rural reality of life in different communities in Ecuador and Cotopaxi, with emphasis on remaining the agriculture, which is closely linked to the production of crops that supply the local and national market. That is why the descriptive methodology was based on participatory research through with the use of techniques such as survey, observation supported by statistical and geographical interpretation to explain clearly the issue investigated was used in this investigation. Additionally, laws were analyzed and generating from the Constitution of the Republic of Ecuador, such as LORSA COOTAD trying to solve the problem of smallholdings through the integration of plots and associated production, but until now the laws have been written only on paper and has not complied with this mandate.